Semiotics of tasting. Axiologies and gustatory processes in the study case of tarte au citron - Tassinari, Carlo Andrea (E|C, 2020)
The tarte au citron meringuée is a classic dessert of French pastry. In this work, we propose to analyze the semiotic process that its tasting gives rise to, starting from a corpus of "major" French recipe books, of tasting variations of the dessert in three tea rooms in the city of Toulouse and interviews with the pastry chefs of the chosen establishments. The study has a twofold objective: on the one hand, to analyze the combination that allows to "normalize" the perceptual experience of the dessert in the "classic" French pastry system, from which it partially deviates; on the other hand, to outline a battery of analytical categories to develop a "semiotics of tasting". At the end of the path, we propose a model of tasting the tarte au citron, focusing on the function that the meringue performs in it and trying to organize the gustatory perceptions in a temporal intertwining of flavors, with particular attention to the "enunciative" value of the consistencies of the dessert.